Ijiri or Grigg: Where do Indonesian Accounting Scholars Go? - Oktavianto, Rizki; Warsono, Sony (Universitas Negeri Malang, 2025)
Financial scandals have raised issues of trust and transparency in the double-entry bookkeeping (DEB) system. This led to adding a third entry to DEB, called triple entry accounting. TEA is not a new idea. This idea has been around since 1982 proposed by Yuji Ijiri, an accounting professor. Also, in 2005, Ian Grigg, a financial cryptographer offered the idea of TEA in a different format. These two different initial concepts of TEA gave rise to TEA research with different alignments. This study conducted a systematic review of 11 TEA articles written by Indonesian accounting scholars and published between 2005 and 2024. This study explores accounting scholars' knowledge domains and their alignment with the original idea of TEA. The results showed that all Indonesian accounting scholars who wrote TEA align with Grigg's initial ideas. This research recommends further research to design ideas for integrating Ijiri and Grigg's TEA concepts to anticipate financial statement fraud.